Análise das práticas de sustentabilidade e de inovação sustentável das indústrias têxteis brasileiras - Maraschin, Andrei de Azambuja (2023)
The following work has the general objective of measuring the practices of sustainable innovation and sustainability applied by companies in the Brazilian textile sector and propose a direction for improvements based on a diagnosis. For the development of the study, it was carried out through four phases composed of: a) Make a Systematic Literature Review on the practices of sustainability and sustainable innovation used in the management and production of the textile industries, b) Identify which are the sustainability practices and sustainable innovation adopted in the management and production of Brazilian textile industries, c) Measure the applicability of sustainability practices and sustainable innovation in the management and production of textile industries and, finally, d) Propose a framework and contributions of innovation practices and sustainability for the textile industries. In large companies, it is possible to perceive the ease of adaptation regarding sustainable practices and innovations. In smaller companies, the concern with the theme is perceived, but due to limitations such as resources and knowledge, it becomes difficult to implement it at the same level. The study proves that sustainable innovation practices and sustainability are important themes that have been highlighted in the literature and in the practice of companies, aiming at reducing waste, reducing the use of raw materials and natural resources and the concern with the lowest levels of pollution to the environment.